Edukasi Nutrisi Berbasis Partisipatif untuk Meningkatkan Pengetahuan Caregiver Lansia dalam Pencegahan Penyakit Tidak Menular di Puskesmas Depok II Sleman - Muftin Annisa; Ayu Wulandari (Jurnal Kesehatan Pengabdian Masyarakat (JKPM), 2024)
Non-communicable diseases (NCDs) are a major cause of morbidity and mortality among older adults, partly influenced by inadequate nutritional intake. Caregivers play a strategic role in managing elderly nutrition; however, gaps in knowledge still affect the quality of care. This community service activity aimed to improve caregivers’ knowledge of elderly nutrition through a participatory-based educational intervention. The activity was conducted on October 26, 2023, at the Depok II Primary Health Center, Sleman Regency, involving 25 elderly caregivers recruited purposively. The intervention was delivered through interactive lectures, discussions, and educational media, including PowerPoint presentations and leaflets, with knowledge assessed using pretest and posttest instruments. The results showed that more than 70% of participants experienced an increase in knowledge, while over 80% actively participated in the discussion sessions. Qualitatively, participants demonstrated an improved understanding of basic elderly nutrition concepts and their application in daily care practices. This activity indicates that participatory-based education is effective in enhancing caregiver capacity as a promotive effort to prevent NCDs in older adults. This intervention model has strong potential for replication and sustainable integration into primary healthcare services.